2015
DOI: 10.3892/mmr.2015.3974
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of gene expression and DNA methylation changes induced by hepatocyte growth factor in human hepatocytes

Abstract: Hepatocellular carcinoma (HCC) is the one of most common malignant tumors. The tumor microenvironment has a role in not only supporting growth and survival of tumor cells, but also triggering tumor recurrence and metastasis. Hepatocyte growth factor (HGF), one of the important growth factors in the tumor microenvironment, has an important role in angiogenesis, tumorigenesis and regeneration. However, the exact mechanism by which HGF regulates HCC initiation and development via epigenetic reprogramming has rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Downregulated in human tumours and positive correlation with patient survival [ 179 , 183 ] Panx2 Hepatocellular carcinoma Potential tumour suppressor. Methylated in cancer samples [ 184 ] Panx2 Neuroblastoma Knockdown in Neuro2a cells increases differentiation [ 21 ] Panx1, Panx3 Basal and squamous skin cell carcinoma Downregulated in BCC and SCC tumours compared to normal skin [ 152 ] …”
Section: Pannexin 1 Upregulation or Gain-of-function In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulated in human tumours and positive correlation with patient survival [ 179 , 183 ] Panx2 Hepatocellular carcinoma Potential tumour suppressor. Methylated in cancer samples [ 184 ] Panx2 Neuroblastoma Knockdown in Neuro2a cells increases differentiation [ 21 ] Panx1, Panx3 Basal and squamous skin cell carcinoma Downregulated in BCC and SCC tumours compared to normal skin [ 152 ] …”
Section: Pannexin 1 Upregulation or Gain-of-function In Cancermentioning
confidence: 99%
“…Consistent with a potential role as tumour suppressor, a recent publication listed PANX2 as one of the methylated genes identified by expression profiling and DNA methylation arrays in hepatocellular carcinomas (HCC) [ 184 ]. In HCC, the hepatocyte growth factor (HGF) upregulates the expression of DNA methyltransferase 1 that results in the hypermethylation and epigenetic repression of potential tumour suppressor genes, including PANX2 .…”
Section: Pannexin 2 As a Tumour Suppressormentioning
confidence: 99%
“…The fetal liver can be compared to a malignant tumor, in the fact that there is rapid changes and growth occurring. It has been shown that HGF treatment of liver cell lines induced alterations in global methylation levels in support of tumorigenesis (Xie et al, ). Investigators reported a hypermethylation of tumor suppressor genes in conjunction with a hypomethylation of several other genes within HGF‐treated cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal liver can be compared to a malignant tumor, in the fact that there is rapid changes and growth occurring. It has been shown that HGF treatment of liver cell lines induced alterations in global methylation levels in support of tumorigenesis (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using brain cancer gene expression database REMBRANDT shows that pannexin‐2 expression levels acts as a post diagnosis survival in patients with glial tumors (Litvin, Tiunova, Connell‐Alberts, Panchin, & Baranova, ). Pannexin‐2 is reported to may be tumor suppressor genes (TSGs) in hepatocellular carcinoma (HCC) (Xie, Sun, et al, ). Moreover, pannexin‐2 expression decreases in a human C6 glioma cell line (Lai et al, ).…”
Section: Pannexins and Oxidative Stress‐related Diseasementioning
confidence: 99%